Characterization of red pigmented yeasts and genes associated with astaxanthin synthesis in Rhodotorula mucilaginosa HL26-1 and Rhodotorula paludigena LL69-1 - Hoondee, Patcharaporn; Tedsree, Nisachon; Phuengjayaem, Sukanya; Kingkaew, Engkarat; Sritularak, Boonchoo; Rojsitthisak, Pornchai; Nakashima, Takuji; Thitikornpong, Worathat; Tanasupawat, Somboon (My University, 2026)
Background: Astaxanthin, a red xanthophyll carotenoid, is a powerful antioxidant, anticancer, and glucose and lipid homeostasis regulator. Some pigmented yeasts belonging to the genus Rhodotorula, the well-known yeast for beta-carotene production, have been reported as natural astaxanthin producers. However, the lack of genomic data on astaxanthin-producing strains within these species hinders the identification of biosynthetic routes, molecular characterization of these pathways, and gene editing applications. Methods: This study explored the diversity and astaxanthin production capability of cultivable pigmented yeast in flower samples. The astaxanthin production ability was inspected by three consecutive methods, including thin-layer chromatography (TLC) for the preliminary step, followed by quantitative spectrophotometry and high-performance liquid chromatography (HPLC) for qualitative validation. The draft genome sequence and astaxanthin-producing genes of astaxanthin-producing yeasts were examined. Results: Twelve of 23 yeasts from floral samples exhibited natural pigmentation, with colors ranging from pinkish-orange to red, and exhibited the potential for astaxanthin synthesis. These yeasts were Rhodotorula paludigena (three strains) and Rhodotorula mucilaginosa (nine strains). Among R. mucilaginosa strains, HL26-1 had the greatest astaxanthin content (104.98 ± 0.13 μg/g DCW) and yield (0.9280 ± 0.0012 mg/L). Strain LL69-1 has the greatest astaxanthin content (251.78 ± 0.27 μg/g DCW) and yield (1.8632 ± 0.0023 mg/L) among R. paludigena strains. The 18.78 Mbp R. mucilaginosa HL26-1 genome includes 5,711 protein-coding genes. Conversely, the R. paludigena LL69-1 genome was 20.99 Mbp, encompassing 6,782 predicted genes. A comprehensive investigation of draft genome sequences of these two strains identified CrtE, CrtYB, CrtI, CrtS, and CrtR as potential astaxanthin transcription genes. Conclusion: Here, our results highlight the outstanding potential of two naturally pigmented yeasts, R. mucilaginosa HL26-1 and R. paludigena LL69-1, for astaxanthin production. Furthermore, our findings provide information on the whole genome and protein-encoded genes associated with astaxanthin production, which serve as valuable biological resources for various biotechnological applications.
Keywords: astaxanthin; astaxanthin synthase; pigmented yeast; Rhodotorula mucilaginosa; Rhodotorula paludigena